No recovery of a large-scale anthropogenic sediment disturbance on the Pacific seafloor after 77 years at 6460 m depth. (February 2022) - Jamieson, Alan J.; Bond, Todd; Vescovo, Victor
Abstract: Habitat restoration and recolonisation of benthic communities after physical perturbation in the deep sea has long been thought to be extremely slow. This study reports on a serendipitous opportunity to survey the current state of a large mechanical disturbance of sediments at 6460 m in the Pacific Ocean. The impact was caused 77 years ago by the sinking of the USS Johnston . The surrounding debris field had little impact on the sedimentary habitat, other than in the provision of artificial hard substrates, while the troughs that formed as the ship impacted the seafloor and slid down the slope of the Philippine Trench were still completely void of animal tracks and burrows, or any observable epifauna, and in some areas subsurface stratification was still exposed at the surface. This suggests that mechanical perturbations of sediments in the deep Pacific may remain ecologically significant for, at the very least, 100 years. Highlights: The WWII Destroyer USS Johnston sunk to 6460 m in the Pacific Ocean in 1944. Exploration of the wreck revealed significant sediment disturbance after 77 years. Troughs left by the impact were void of animal tracks or any observable epifauna. Perturbations of sediments in the deep Pacific may remain ecologically significant for over a century. In some areas subsurface stratification was still exposed at the surface.